Case of Crack Dynamics and Wallner Line in Fracture Analysis - Xiaolu Zhu (Jixie chuandong)
Abstract In the case of failure analysis of fracture of crankshaft with material 42CrMo, forged, tempered and nitriding treatment, it is found that there is an abnormal phenomenon of intersection of the scallop lines on the fracture surface. This is not possible in the general fracture surface. The crack dynamics and the theory of Wallner line are used to analyze the abnormal phenomenon, the crack at the source of fracture fatigue will produce stress wave in the material and propagate on the surface where the crack is located. When the crack encounters a discontinuous surface, a transverse stress wave is generated, thus forming a second set of concentric arcs centered at the wave source. This makes it possible for the shellfish lines to intersect. For the first time, it is observed that Wallner line cannot only appear on fracture surfaces of metallic and non-metallic brittle materials. It illustrates that Wallner line can also appear on the fracture surface of quenched and tempered steel.